Coir-Krishimithra: An Apposite Medium for Cultivation of Vegetable/ Medicinal/ Ornamental Plants - Radhakrishnan, S.; Ravindranath, Anita Das; Reghuvaran, Abesh; Geena, M. G. (International Coconut Community Journal, 2018)
Coir pith is a by-product of the coir fibre processing industry. Accumulation of coir pith leads to an environmental concern and its management is a major problem with all coir industrialists. Therefore biodegradation of coir pith is an essential requirement to control pollution. Coir pith is a potential wealth and can be converted into valuable organic manure by microbial degradation. A method of composting of coir pith with urea has been developed by Coir Board which uses a fungus viz., Pithplus (Pleurotus sajor caju). Application of urea releases higher concentration of ammonia in the soil making it more acidic and retards soil natural fertility. Hence an alternative cost effective nitrogen supplement needs to be developed as a substitute to urea for composting of coir pith. Coir pith can be converted to effective organic manure with the use of fungus (Pleurotus sajor caju) along with the addition of nitrogen supplements like Azolla, Neem cake and Fish waste in 1:1:1 proportion. The present study aims at the formulation of bioorganic manure from coir pith avoiding urea in the composting. Overall assessment on the physico chemical properties of the biodegraded coir pith leads to the conclusion that a combination of Azolla, Neem cake and Fish waste in 1:1:1 proportion was found to be efficient in lignin degradation and contribute to novel changes in coir pith. A study was conducted to evaluate the competence of biocompost thus produced for the cultivation of Amaranthus and Groundnut. Studies confirmed that Coir-KrishiMithra can be used as an effective growing media and hence, the use of Coir-KrishiMithra, a 100% organic manure can be entertained in homes, nurseries and fields for the cultivation of plants mainly vegetables; thereby promoting the eco-friendly organic cultivation and minimize the environmental pollution caused by chemical fertilizers.